Genuine impact of 18F-fluorodeoxyglucose positron emission tomography with contrast-enhanced computed tomography in clinching the diagnosis and follow-up response assessment of vascular graft infections - Sivathapandi, Thangalakshmi; Amalachandran, Jaykanth; Elangovan, Indirani; Simon, Shelley; Patel, Asra; Nikita (World Journal of Nuclear Medicine, 2020)
Vascular graft infection (VGI) is a rare and severe complication after vascular surgery associated with significant morbidity and mortality, but the diagnosis is not always straightforward due to its variable and nonspecific clinical signs. Computed tomography (CT) scan is considered to be the diagnostic tool of choice for advanced VGI, but there is a high incidence of false-negative results, especially in low-grade infections. 18F-Fluorodeoxyglucose positron emission tomography with contrast-enhanced CT (18F-FDG PET-CT) imaging can serve as an effective alternative tool for assessment of suspected VGI and also provide accurate anatomic localization of the infective focus. Here, we describe three cases of VGI with various clinical presentations where the site of infection was diagnosed, confirmed, and documented with the help of 18F-FDG PET-CT imaging.
Keywords: Aortic root infection; fluorodeoxyglucose positron emission tomography with contrast-enhanced computed tomography; vascular graft infection